2021
DOI: 10.1039/d1an00993a
|View full text |Cite
|
Sign up to set email alerts
|

A facile aptamer immobilization strategy to fabricate a robust affinity monolith for highly specific in-tube solid-phase microextraction

Abstract: Developing functional affinity monolithic column towards in-tube solid-phase microextraction (IT-SPME) for the selective sample pretreatment is critical. Herein, a high-performance capillary affinity monolithic column with ultra-high aptamer coverage density was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Therefore, the adsorbent of the in-tube SPME system plays a key role in improving the selectivity, sensitivity, and enrichment capacity. In this context, porous polymer adsorbents have attracted consid-erable attention because of their excellent enrichment performances during sample preparation [31][32][33]. In terms of their preparation, some studies have indicated that thiolyne polymerization is a simple route that is insensitive to oxygen inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the adsorbent of the in-tube SPME system plays a key role in improving the selectivity, sensitivity, and enrichment capacity. In this context, porous polymer adsorbents have attracted consid-erable attention because of their excellent enrichment performances during sample preparation [31][32][33]. In terms of their preparation, some studies have indicated that thiolyne polymerization is a simple route that is insensitive to oxygen inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…After redissolving in ultrapure water and being filtered, it has been enriched by online IT-SPME (Figure C), and four enriched bisphenols (BPs) has been determined by the combined HPLC-UV . To effectively avoid the HPLC blockage, other liquid food samples, such as beers and functional drinks, have been carefully treated before the IT-SPME and instrument quantification processes.…”
Section: Spme In Food Analysismentioning
confidence: 99%
“…1,49 To overcome this drawback, Zhao et al proposed a strategy for DNA adsorption using SiO 2 , which avoids non-specific binding of the aptamer while maintaining its structural flexibility. 99 However, SiO 2 does not possess good electrical conductivity, which is essential for electron transfer in aptamer-based biosensors. 96 In 2014, a solution was proposed to address the problem by coating the SiO 2 surface with a layer of graphene.…”
Section: Linkers and Spacersmentioning
confidence: 99%